2008
DOI: 10.1137/070681235
|View full text |Cite
|
Sign up to set email alerts
|

Constraint Nondegeneracy, Strong Regularity, and Nonsingularity in Semidefinite Programming

Abstract: Abstract. It is known that the Karush-Kuhn-Tucker (KKT) conditions of semidefinite programming can be reformulated as a nonsmooth system via the metric projector over the cone of symmetric and positive semidefinite matrices. We show in this paper that the primal and dual constraint nondegeneracies, the strong regularity, the nonsingularity of the B-subdifferential of this nonsmooth system, and the nonsingularity of the corresponding Clarke's generalized Jacobian, at a KKT point are all equivalent. Moreover, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 50 publications
3
78
1
2
Order By: Relevance
“…In order to analyze the rate of convergence of the Newton-CG augmented Lagrangian method to be presented in Section 4, we need the following result which characterizes the Lipschitz continuity of T −1 g at the origin. The result we establish here is stronger than that appeared in Proposition 15 of [8].…”
Section: Assumption 1 Problem (P ) Satisfies the Slater Conditioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In order to analyze the rate of convergence of the Newton-CG augmented Lagrangian method to be presented in Section 4, we need the following result which characterizes the Lipschitz continuity of T −1 g at the origin. The result we establish here is stronger than that appeared in Proposition 15 of [8].…”
Section: Assumption 1 Problem (P ) Satisfies the Slater Conditioncontrasting
confidence: 66%
“…In spite of that, under mild conditions, a linear rate of convergence analysis is available (superlinear convergence is also possible when σ k goes to infinity, which should be avoided in numerical implementations) [33]. However, recent studies conducted by Sun, Sun, and Zhang [37] and Chan and Sun [8] revealed that under the constraint nondegenerate conditions for (D) and (P ) (i.e., the dual nondegeneracy and primal nondegeneracy in the IPMs literature, e.g., [1]), respectively, the augmented Lagrangian method can be locally regarded as an approximate generalized Newton method applied to a semismooth equation. It is this connection that inspired us to investigate the augmented Lagrangian method for SDPs.…”
Section: Introductionmentioning
confidence: 99%
“…Constraint nondegeneracy plays a very important role in optimization, see [3, Def. 5], [10,Def. 9], and [37, Sect.…”
Section: Existence Of Optimal Dualmentioning
confidence: 99%
“…Since y is an optimal solution of (8), A := Π K n + (D + Diag(y)) is the optimal solution of (3) by (10). Obviously, A is feasible with respect to the constraints of (3).…”
Section: Generalized Jacobian Ofmentioning
confidence: 99%
“…We refer to [8] for more references, results, and comments on its application to SDP. We describe it below.…”
Section: Nonsingularity Of ∂F (Y)mentioning
confidence: 99%